A Good Place for What? Placing "Value" in Youth Centers. (19th May 2022) - Sharpe, Erin K.; Lashua, Brett; van Ingen, Cathy
Abstract: In this article, we investigate the discursive context of community-based youth centers to critically interrogate ideas and practices concerning leisure, youth, and youth centers. Using publicly available documents and data collected with youth at two community-based youth centers, we ask, what is the "good"' they do for young people, and how do young people negotiate these discourses? We argue that youth centers operate in a discursive tension, constructed as a place to change by the (organizational) bodies that establish them, and a place to chill by the (youth) bodies that use them. We trace how these discourses entered into the everyday lived contexts of youth centers, including their program logics, measures of success, and constructions of youthful subjectivities. We close with a discussion of the implications of the research in terms of how youth and recreation practitioners might use youth centers to support young people's leisure.